1992
DOI: 10.1203/00006450-199202000-00011
|View full text |Cite
|
Sign up to set email alerts
|

d-α-Tocopheryl Polyethylene Glycol-1000 Succinate Enhances the Absorption of Vitamin D in Chronic Cholestatic Liver Disease of Infancy and Childhood

Abstract: ABSTRACT. Rickets and osteopenia, common problems in chronic childhood cholestasis, have been attributed to vitamin D malabsorption leading to reduced serum levels of 25(0H)-vitamin D. d-a-Tocopheryl polyethylene glycol-1000 succinate (TPGS), a water-soluble form of vitamin E, forms micelles at low concentration. We evaluated the potential role of TPGS in enhancing vitamin D absorption in eight children (aged 5 mo to 19 y) with severe chronic cholestasis (three extrahepatic biliary atresia, three nonsyndromic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…24 When TPGS is coadministered with other FSV, enhanced absorption of the unmodified vitamins has been observed in the setting of significant cholestasis. 7 This property formed the basis for the commercially available liquid preparations of multiple FSV (with larger doses of FSV than standard multivitamin preparations) suspended in TPGS that were used in this study. Although initially formulated for use in cystic fibrosis, these preparations had the potential for relatively simplified administration of all FSV to infants with cholestasis and were thus chosen as the standard form of vitamin supplementation for infants with BA in this prospective study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 When TPGS is coadministered with other FSV, enhanced absorption of the unmodified vitamins has been observed in the setting of significant cholestasis. 7 This property formed the basis for the commercially available liquid preparations of multiple FSV (with larger doses of FSV than standard multivitamin preparations) suspended in TPGS that were used in this study. Although initially formulated for use in cystic fibrosis, these preparations had the potential for relatively simplified administration of all FSV to infants with cholestasis and were thus chosen as the standard form of vitamin supplementation for infants with BA in this prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…The TPGS (an amphipathic molecule) potentially serves to enhance absorption of FSV that are comixed in these preparations. 7 The vitamin composition of the 2 preparations differed in that AquADEKs contained more vitamin A as b carotene, 25% more vitamin E, and 4 …”
Section: Vitamin Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…TPGS has been used to enhance absorption of poorly soluble drugs, such as cyclosporine or amprenavir (Agenerase r capsules). Argao et al [25] showed that co-administration of TPGS and vitamin D 3 increased serum 25(OH)D in cholestatic patients. The role of TPGS, however, in normalizing the vitamin E status in malabsorption may be greatly enhanced by utilizing its ability to achieve micellar solubilization and increase absorption of the natural tocols.…”
Section: Discussionmentioning
confidence: 98%
“…Befunde bei Patienten mit chronischer Cholestase sprechen zudem fª eine Steigerung der Vitamin-D-Absorption nach Applikation von Vitamin-E-Analoga [3]. Molekularbiologische Untersuchungen aus jª Zeit unterstreichen zudem die Bedeutung von c~-TocopherolTransferprotein (c~-TTP) als wesentlichem Faktor fª einen ausreichenden antioxidativen Schutz ron Neuronen [24].…”
Section: Laboruntersuchungenunclassified